2018
DOI: 10.1016/j.resuscitation.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

One-year survival after in-hospital cardiac arrest: A systematic review and meta-analysis

Abstract: One-year survival after in-hospital cardiac arrest is poor. Survival is higher in patients admitted to cardiac wards. The time trend between 1985-2018 has shown a modest improvement in one-year survival rates. Research into IHCA population characteristics might elicit the issue of heterogeneity and stagnated survival over the past decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
116
5
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 66 publications
9
116
5
9
Order By: Relevance
“…Especially the age criteria are quite stringent, and therefore likely affect the apparent survival [42], given the average age of the CPR population [43]. Moreover, the nding that we found substantially less heterogeneity in survival rates between studies than a systematic review of the CCPR literature [1,2] also supports the hypothesis that this is a selected population. Nevertheless, part of the difference might be explained by the effect of ECPR versus CCPR on outcome [45][46][47].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Especially the age criteria are quite stringent, and therefore likely affect the apparent survival [42], given the average age of the CPR population [43]. Moreover, the nding that we found substantially less heterogeneity in survival rates between studies than a systematic review of the CCPR literature [1,2] also supports the hypothesis that this is a selected population. Nevertheless, part of the difference might be explained by the effect of ECPR versus CCPR on outcome [45][46][47].…”
Section: Discussionsupporting
confidence: 71%
“…Although neurological outcome is good, it remains inconclusive whether neurological outcome of patients receiving ECPR is better than patients receiving CCPR. We did nd a lower percentage of "good" neurological outcome (CPC1-2) than in a systematic review in a conventional CPR population [2]. However, in this review CPC score was a secondary outcome.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…7 A recent meta-analysis of global IHCA studies found a pooled 1-year survival rate of 13.4%. 21 This meta-analysis included studies as early as 1985, which may explain some of the difference seen. We recognise that the long-term survival of our cohort was quite high, however, this was the first study of a regional cohort so there is no specific benchmark for comparison.…”
Section: Long-term Survivalmentioning
confidence: 99%
“…1 The incidence of IHCA is 1-6 events per 1000 hospital admissions [2][3][4] and recent meta-analyses showed a pooled survival to discharge of 15% (ranging from 3% to 40%) and a one-year survival of 13% (ranging from 4% to 69%). 5,6 Patient-specific factors associated with survival are age, 7,8 comorbidities [9][10][11][12] and presence of shockable rhythm. 13 A possible advantage for patients suffering IHCA versus OHCA is that hospitals are equipped with advanced life support teams, who could employ extracorporeal cardiopulmonary resuscitation (ECPR) using veno-arterial extracorporeal membrane oxygenation (VA-ECMO).…”
Section: Introductionmentioning
confidence: 99%